Enhancing geoid modelling for accurate local geoid determination in Lagos Island: A combined GNSS and levelling approach, Eti-Osa Local Government Area, Lagos State, Nigeria - TATA, Herbert; OMODEJO, Olamilekan Babatunde (Contributions to Geophysics and Geodesy, 2024)
Lagos Island faces challenges from coastal hazards and inadequate infrastructure, making precise geoid modelling essential for urban planning, flood risk assessment, and infrastructure development. This study addresses discrepancies in height references and emphasizes the need for accurate geoid data to support spatial planning and disaster management. The main objective is to create a geoid model tailored to Lagos Island’s unique geography and infrastructure needs. The research combines the Global Navigation Satellite System (GNSS) and levelling data which created a reliable framework for determining geoid heights with high precision across Lagos Island. The methodology uses spirit levelling to obtain orthometric heights and GNSS technology, precisely Promak2 differential GNSS Receiver, to collect positional data. Ninety stations were surveyed to ensure comprehensive area coverage. This data was used to develop a geoid model through geometrical interpolation, accurately representing the local geoid surface. In the independent test, where 10 points were excluded from interpolation, the modelled geoid heights showed an RMSE of 0.2 metres, with the largest and smallest absolute deviations being 0.4 metres and 0.01 metres, respectively. In the non-independent test, where all points were used for interpolation, the comparison between the computed (observed) and modelled geoid heights at the same points showed a mean deviation of −0.3 metres. The RMSE and standard deviation were both 0.1 metres, confirming the model’s accuracy in determining the local geoid. This demonstrates its suitability for precise local geoid determination in Lagos Island, providing a valuable tool for spatial analysis, infrastructure planning, and disaster mitigation. The study highlights the importance of integrating traditional surveying techniques with modern GNSS technology to address coastal urban challenges.